Efeito de um protótipo inibidor da enzima Dipeptidil peptidase 4 (IDPP-4) em modelo experimental de homeostasia da glicose e resistência à insulina in vivo - Roriz, Raquel Nascimento da Silva (2025)
Estimates indicate that by 2040, one in ten adults will have diabetes. Dipeptidyl peptidase 4 (DPP-4) inhibitors prevent the proteolysis of the active form of incretin hormones (GIP and GLP-1), known to regulating blood glucose levels. However, adverse effects have been reported in this class of drugs, which limit their use, and new molecules may improve the therapeutic effect. Thus, the objective of this study is to investigate the hypoglycemic activity of DPP-4 inhibitors beta-aminohydrazines, beta-amino-acylhydrazones (LASSBio-2123, 2124, 2125, 2129 and 2130), from the Laboratory of Evaluation and Synthesis of Bioactive Substances (LASSBio®), located at the Institute of Biological Sciences (ICB) of the Federal University of Rio de Janeiro (UFRJ), using pharmacological and molecular tools. For these purposes, the Glucose Tolerance Test (GTT) of the compounds (LASSBio-2123, 2124, 2125, 2129 and 2130; at doses of 0.1, 1.0 and 10 mg/kg i.p.) and the induction of insulin resistance by dexamethasone were performed in male C57/Bl6 mice subjected to CEUA-NPDM (Protocol 17010720-0). The following were also analyzed: lipid profile, glycogen levels, GLUT4 mRNA. Predictive data on pharmacokinetics (SwissADME) and toxicology (ProTox-II) were obtained from specialized software. The cell viability test was performed in mouse pancreatic insulinoma cells, MIN6. All data were expressed as mean ± standard error of the mean. The unpaired t-test was used to analyze statistical differences between two groups and one-way ANOVA followed by the Bonferroni test for more than two groups using Graphpad Prism 8 software (GraphPad Software Inc., San Diego, CA, USA). In the GTT, among all sitagliptin analogues that were evaluated, the compound LASSBio-2129 showed a marked reduction in glycemia and increased muscle and liver glycogen levels, and was therefore chosen for the other analyses. LASSBio-2129 (10 mg/kg) improved insulin resistance and increased muscle GLUT4 mRNA levels. In in sílico studies, the compound LASSBio-2129 showed an adequate profile because it has a low molecular weight, is absorbed in the GIT, and is not a substrate for P-gp or the main CYP enzymes. In addition, it was shown to be inactive for: hepatotoxicity, immunotoxicity and mutagenicity, being slightly active for neurotoxicity. The compound LASSBio-2129 showed cell viability in cell culture. Finally, our results demonstrate that among the compounds analyzed, LASSBio-2129 presented the best dose-response curve in glycemia, improved insulin resistance and has biological activities similar to those of sitagliptin at the same pharmacological dose (10 mg/kg). Furthermore, LASSBio-2129 demonstrated more attractive pharmacokinetics and less prominent toxic effects when compared to sitagliptin.